Intensity of sulfonitric treatment on multiwall carbon nanotubes - Gómez, Sofía (2017)
We present a study of sulfonitric treatment and its effect on MWCNTs at different temperatures (90, 110, 130 and 150°C) using DRX, XPS, FTIR, Raman spectroscopy, TEM and zeta potential. It was found that oxidation starts with the C-C and C-H bonds generating different oxidized groups from alcohol to carboxylic acid, following a sequential oxidation. Given that heterocoagulation needs a maximum zeta potential gap between the ceramic and the MWCNT surface and it significantly exist a risk of manipulate acids at high temperature it is recommended to use acid treatment of CNT at 110 °C for generating ceramic composites by heterocoagulation.